INTEGRATED RISK MANAGEMENT MODEL RELATED TO OCCUPATIONAL SAFETY IN MULTI-STOREY BUILDINGS - Dwi Iryaning Handayani (Journal of Engineering and Management in Industrial System, 2018)
The goal of this research is to apply risk management model related to the Occupational Health and Safety (OHS) by integrating Causal Effects Diagram (CED), Analytic Network Process (ANP) and Interpretive Structural Modeling (ISM). The research method consists of three (3) stages. Stage 1) Using CED method to know the correlation between the risks and their causes. Stage 2) Making an assessment by using Analytic Network Process (ANP) with Software Matlab, stage 3) Interpretive Structural Modeling (ISM) is used to get the model of connectivity in mitigation of occupational accident. From ANP method, it is clear that the dominant potential risk in structural phase is 44% and the highest cause of accident by human factor is 77%, and it is due to the unsafe behavior. ISM method is used to know the mitigation in reducing the occupational accident risks, namely improvement of Occupational Health and Safety (OHS) management, Each Scaffolding establishment must be inspected by a certified expert, the working methods must obey the Indonesian National Standard (SNI), The risk control should be done in relation to potential cause of occupational accident which can minimize the risk on construction work (zero accident).